(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This article, having studied and analyzed sources on family history, discusses the idea that the ideas, thoughts, and reflections on the subject in the works of our scholars and thinkers serve as an important methodological resource for organizing the education of young people in today’s turbulent times, and therefore, the ways to improve their use in the upbringing of young people, especially in the process of preparing them for family life.